Why and how to build back better in shrinking territories?. Issue 4 (15th January 2019) - Di Giovanni, Grazia; Chelleri, Lorenzo
Abstract : Purpose: The purpose of this paper is to explore the concept of build back better (BBB) in contexts affected by depopulation and shrinking economies discussing how and if its principles are able to drive the recovery pattern toward a sustainability re-development path. Design/methodology/approach: BBB principles' usefulness in driving toward a sustainable post-disaster recovery has been tested in L'Aquila's area (Italy) – severely affected by an earthquake in 2009 – through interviews and analyses of reconstruction plans and policies. Findings: Although most of the BBB principles can be recognized within the intentions of plans and policies, the recovery process highlights a major fallacy in addressing the pre-disaster socio-economic stresses inducing to shrinkage and depopulation development lock-ins. Practical implications: Although most of the principles can be recognized in the intentions of plans and policies, the recovery process highlights a main fallacy of the "BBB paradigm": the need of addressing pre-disaster socio-economic stresses while recovering from the shocks was not explicitly nor implicitly addressed. Originality/value: Shrinkage as a process of territorial transformation has been little explored in relation to natural hazards and post-disaster contexts. Indeed, while from one side BBB concept and principles drive toward a potential mitigation of the main risks while re-building, it results challenging to overcome the built environment re-building priorities to question whether, what and how to re-build while investing in socio-economic recovery. Reverting, or accepting, shrinkage could indeed implies to not build back part of the urban fabric, while investing in skills and capacity building, which, in turn, would be difficult to justify through the reconstruction budget. The tension between re-building (better, the built environment) and re-development (skills and networks, at the expense of re-building) is critical when BBB faces disasters happening in shrinking territories.